2010
DOI: 10.1007/s00586-010-1659-4
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic spondylitis in the elderly: a report from Japan with the most aging society

Abstract: Pyogenic spondylitis can be life-threatening for elderly patients. To discuss the characteristics of the disease in the elderly, medical records of 103 consecutive cases of pyogenic spondylitis were reviewed. Of these, 45 cases were 65 years of age or older, and these 45 cases were enrolled into further study. In this study, the proportion of elderly patients among the total number with pyogenic spondylitis was 43.7%, and this figure has increased with the passing of time as follows: 37.5% (1988-1993), 44.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 11 publications
4
23
0
7
Order By: Relevance
“…Typically, the onset of pyogenic spondylitis is characterized by back pain accompanied by fever (Tsiodras and Falagas 2006;Fantoni et al 2012). However, the insidious type of onset has become more common in Japan recently, reported between 16% and 65% (Ozawa 2008;Yoshimoto et al 2011). In the present study, about one-fourth of the patients showed this type of onset.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Typically, the onset of pyogenic spondylitis is characterized by back pain accompanied by fever (Tsiodras and Falagas 2006;Fantoni et al 2012). However, the insidious type of onset has become more common in Japan recently, reported between 16% and 65% (Ozawa 2008;Yoshimoto et al 2011). In the present study, about one-fourth of the patients showed this type of onset.…”
Section: Discussionsupporting
confidence: 54%
“…The onset type was classified using the modified Kulowski's classification (1936): 1) acute: onset with typical acute inflammatory symptoms such as high fever, severe back pain, and stiffness of the spinal column; 2) subacute: onset with slight fever and back pain; 3) insidious: unknown time of onset with only mild local symptoms such as back pain continuing for a certain period, without accompanying fever (Ozawa 2008;Yoshimoto et al 2011); and 4) unclassified.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, minimally invasive and endoscopic surgeries are being promoted [9,11]. Treatment of infectious spondylodiscitis in children, geriatric patients, and patients with multiple risk factors can be very challenging and gives cause for intense discussions [10,13,19].…”
mentioning
confidence: 99%